Comparison of recovery and outcome after left and right colectomy. (18th January 2019) - Grass, F.; Lovely, J. K.; Crippa, J.; Ansell, J.; Hübner, M.; Mathis, K. L.; Larson, D. W.
Abstract: Aim: The present study aimed to compare functional recovery and surgical outcomes after left and right colectomies. Method: Consecutive elective left and right colon resections for benign and malignant indications, performed between 2011 and 2016 and recorded in a prospectively maintained enhanced recovery database, were analysed. Demographic and surgical items, as well as functional recovery and 30‐day complications, were compared between left‐sided and right‐sided colectomies. Multivariable analysis was performed to identify risk factors for postoperative ileus (POI). Results: In total, 1001 left and 1041 right colectomies were comparable regarding demographic factors; only body mass index (BMI) was higher in patients undergoing left‐sided resections (> 30 kg/m 2 : 33% vs 27%, P  = 0.004). Malignancy (29% vs 67%, P  < 0.001) and Crohn's disease (1% vs 31%, P  < 0.001) were preponderant in right colectomies, whereas diverticular disease (68% vs 1%, P  < 0.001) was the most common indication for left colectomy. Compliance with the enhanced recovery pathway (ERP) was comparable. While the minimally invasive approach was the preferred approach for both sides (61% vs 64%, P  = 0.158), left colectomies took longer (180 ± 80 min vs 150 ± 70 min, P  < 0.001), needed more perioperative fluids (3.1 ± 1.4 l vs 2.7 ± 1.5 l, P  < 0.001) and resulted in greater postoperative weight gain (3.9 ± 6.5 kg vs 2.6 ± 6 kg, P  = 0.025). Crohn's disease (OR = 2.64, 95% CI: 1.27–5.46) and fluid overload (OR = 2.02, 95% CI: 1.06–3.82) were independent risk factors for POI. Conclusion: Despite equal ERP compliance, postoperative ileus was higher after right‐sided colectomies. This finding was associated with Crohn's disease and fluid overload.